Assessment of a cost-optimal power system fully based on renewable energy for Iran by 2050 – Achieving zero greenhouse gas emissions and overcoming the water crisis. (February 2020) - Ghorbani, Narges; Aghahosseini, Arman; Breyer, Christian
Abstract: Transition of Iran's power system from 2015 to 2050 through three scenarios was modelled. Two scenarios present a transition pathway towards a fully renewable run power system with different involved sectors (power only, power sector coupled with desalination and non-energetic gas sectors). The third scenario is based on the country's current policies. The energy model performs an hourly resolution to guarantee meeting energy demand for every hour of the whole year. It is found that renewable energy resources in Iran can satisfy 625 TWh of power sector demand in 2050. Further, it is technically and economically feasible that electricity demand for supplying 101 million m 3 desalinated water and 249 TWhLHV synthetic natural gas for non-energetic industrial gas demand can be supplied via renewable resources. A 100% renewable power system with 54 €/MWhel levelised cost of electricity (LCOE) is more cost-effective than the current power system in Iran with 88.3 €/MWhel LCOE in 2015. LCOE of the system can decrease further and reach to 41.3 €/MWhel in 2050 via sector coupling. On the other hand, the current policies of the country lead to an inefficient power system with a LCOE of 128 €/MWhel and 188 Mt/a emitted CO2 in 2050. Highlights: Transition to 100% renewable energy power system for Iran by 2050. Zero GHG emission system at an optimal cost. Desalination system based renewable energy a potential solution for water crisis. Multi-node approach with hourly resolution.